2021
DOI: 10.1002/oby.23164
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiles of Shift Workers and Day Workers: A Cross‐Sectional Study

Abstract: Objective The purpose of this study was to characterize the metabolomic profiles of shift workers and day workers and to discover the effect of shift work on workers’ metabolic health. Methods A total of 824 participants aged 25 to 55 years were recruited, and 485 (275 shift workers and 210 day workers) completed the study. The mean age of the shift workers was 37.32 (5.53) years old, and that of day workers was 36.50 (7.83) years old. Serum and salivary samples were collected for the detection of key biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
(46 reference statements)
6
8
0
Order By: Relevance
“…Serum metabolites in shift workers were previously investigated on 60 subjects from China (25). Shift workers had altered levels of several lipids, including some glycerophospholipids and sphingolipids, as observed in our study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Serum metabolites in shift workers were previously investigated on 60 subjects from China (25). Shift workers had altered levels of several lipids, including some glycerophospholipids and sphingolipids, as observed in our study.…”
Section: Discussionsupporting
confidence: 66%
“…The first one analyzed urinary metabolites, and found altered long-chain acylcarnitines, three amino acids, and one sphingomyelin (24) in night shift workers as compared to day workers, based on both crude and adjusted models. The second study evaluated serum metabolites and identified 76 of them in shift workers (including L-tryptophan, acylcarnitines, and several fatty acids) which may represent important biomarkers of impaired lipid metabolism, leading to weight gain and central obesity (25). As such, evidence on this topic is still limited and further studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…94,95 Other studies have also suggested that individuals who work night shifts are at a higher risk of weight gain and obesity due to disturbances in tryptophan metabolism. 96,97 Therefore, our data demonstrated that irregular LD cycles induced hepatic tryptophan metabolism disorders in both CD and ABX mice, particularly under constant darkness (LD0/24). The tryptophan metabolism pathway emerged as a critical pathway mediating interactions between GM, CCs, and the host, influencing immune function and metabolic homeostasis in response to irregular LD cycles.…”
Section: Different Ld Cycles Had Varying Metabolic Patterns In the Livermentioning
confidence: 60%
“…In our study, D-Glutamine and D-glutamate metabolism was decreased in the DHC group, consistent with the above study. In a metabolomic study of 210 day workers and 275 shift workers, shift workers were more likely to have weight gain and central obesity and were at higher risk for impaired lipid metabolism, accompanied by altered ubiquinone and other terpenoid-quinone biosynthesis [ 51 ]. It was found that the decreased expression of CoQ was observed in diabetic rats as well as obese mice [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%